2016
DOI: 10.5194/acp-16-7587-2016
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires in northern Eurasia affect the budget of black carbon in the Arctic – a 12-year retrospective synopsis (2002–2013)

Abstract: Abstract. In recent decades much attention has been given to the Arctic environment, where climate change is happening rapidly. Black carbon (BC) has been shown to be a major component of Arctic pollution that also affects the radiative balance. In the present study, we focused on how vegetation fires that occurred in northern Eurasia during the period of 2002–2013 influenced the budget of BC in the Arctic. For simulating the transport of fire emissions from northern Eurasia to the Arctic, we adopted BC fire e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 72 publications
(98 reference statements)
2
56
0
Order By: Relevance
“…16b): that is, about a quarter of the total BC emitted from Siberian 25 fires was transported into the Arctic. This estimate of the transport efficiency is comparable with that (about 30 %) obtained by Evangeliou et al (2016) for BC emitted from fires in Asia in the summer periods 2012-2013. Our results show that the transport efficiency was not constant across the different months.…”
Section: Bc Transport Into the Arcticsupporting
confidence: 76%
See 1 more Smart Citation
“…16b): that is, about a quarter of the total BC emitted from Siberian 25 fires was transported into the Arctic. This estimate of the transport efficiency is comparable with that (about 30 %) obtained by Evangeliou et al (2016) for BC emitted from fires in Asia in the summer periods 2012-2013. Our results show that the transport efficiency was not constant across the different months.…”
Section: Bc Transport Into the Arcticsupporting
confidence: 76%
“…For example, according to the FEI-NE inventory recently developed by Hao et al (2016), the annual BC emissions from fires in northern Eurasia in the period of 2002-2015 are, on average, a factor of 3.2 larger than those given by the GFED4 (van der Werf et al, 2017) inventory. Using 15 the FEI-NE inventory in the FLEXPART Lagrangian particle dispersion model, Evangeliou et al (2016) found the model results to be in a reasonable agreement with surface BC concentrations observed at several Arctic stations in the period [2002][2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013]. On the other hand, a Bayesian inverse modeling analysis based on carbon isotope characterization of BC measurements at Tiksi (East Siberian Arctic) from April 2012 to April 2014 revealed that the best fit of the FLEXPART data to the observations was achieved by reducing the fire emissions given by GFED4 by 53 % (Winiger et al, 2017); this 20 estimate may, however, reflect uncertainties in the spatial distribution of the GFED4 emissions, as the sensitivity footprints in this particular study cover only a part of Siberia (Winiger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This BC emission inventory is essential for modeling air quality in high latitudes and ice and snow melting in the Arctic. The dataset has been used for studying the transport and deposition of BC on the Arctic from 2002 to 2013 (Evangeliou et al, 2016). The study found that approximately 8.2 ± 2.7 % of the BC emitted by northern Eurasian fires was deposited on Arctic ice during the period of 2002-2013, accounting for 45-78 % of the BC deposition from all the sources (Evangeliou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The dataset has been used for studying the transport and deposition of BC on the Arctic from 2002 to 2013 (Evangeliou et al, 2016). The study found that approximately 8.2 ± 2.7 % of the BC emitted by northern Eurasian fires was deposited on Arctic ice during the period of 2002-2013, accounting for 45-78 % of the BC deposition from all the sources (Evangeliou et al, 2016). About 42 % of the BC emitted during spring and summer was deposited on Arctic ice, which is the most effective period for acceleration of ice and snow melting.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Stohl et al (2013) and Sand et al (2016) raised questions about prior studies by identifying the importance of seasonally varying residential heating and by suggesting a significant overlooked source from gas flaring in high-latitude regions. In addition to anthropogenic emissions, biomass burning is another important source of Arctic BC Warneke et al, 2009;Yttri et al, 2014;Evangeliou et al, 2016), yet its contribution remains uncertain. Furthermore, evidence is emerging that the BC observations to which many prior modelling studies compared may have been biased by 30 % (Sinha et al, 2017) or a factor of 2 due to other absorbing components in the atmospheric aerosol.…”
Section: Introductionmentioning
confidence: 99%